The Role of Saving Interest in the Influence of Service Quality on Customer Satisfaction (CV. Era Digital Nusantara, 2024)
This study aims to analyze the effect of service quality on customer satisfaction with interest in savings as an intervening variable at Bank Sumsel Babel Syariah KC Palembang. The population in this study were all customers of Bank Sumsel Babel Syariah Palembang Branch Office as many as 1.2 million people. The sample obtained was 80 respondents. To analyze the data, this study used the help of the Smart PLS 4 application program. The results showed that service quality has a direct effect on customer satisfaction, service quality has a direct effect on saving interest, saving interest directly affects customer satisfaction and service quality affects customer satisfaction through saving interest. The conclusion that service quality and saving interest directly affect customer satisfaction, saving interest directly affects customer satisfaction and saving interest is able to mediate the effect of service quality on customer satisfaction.